Examining Teacher Negligence, Hostile Aggression On Student Worldview And Self-Esteem - Beenish Sarfraz Syed , Dr. Ammara Nawaz Cheema , Dr. Somayya Komal , Dr. Zahid Iqbal , Dr. Shahid Iqbal (Migration Letters, 2024)
The regression models used in this study attempted to determine the impact of perceived teacher rejection behavior on student psychological well-being. The first model focused on teacher negligence and its relationship with students’ negative worldviews. The investigation demonstrated a significant relationship (F=16.62, p<.000) between teacher negligence and negative world view among students (β=0.180, p<.000). Moreover, the second model, which examined perceived teacher hostile aggression and its relationship on student negative self-esteem, revealed no statistically significant findings (F=0.441, p=.507), suggesting that teacher hostility is not a major predictor of student negative self-esteem. The results presented reveal that, while negligent teaching practices may contribute to students’ poor perceptions of the world, aggressive teacher [1]behavior does not appear to have a major impact on student self-esteem. These findings highlight the importance of perceived teacher-student interactions in determining student well-being and highlight the need for interventions focused at fostering positive teacher behaviors to improve outcomes for students. Further research is warranted to explore additional factors influencing teacher-student dynamics and their impact on student psychological health.